Relative preference mapping (RPM) – A novel approach for simultaneous 2D relative scoring of difference and liking to identify consumer preference for innovative wine styles. (July 2020) - Adjei, M.Y.B.; Saliba, A.J.; Carr, T.; Hardie, W.J.; Heymann, H.
Highlights: A valid and rapid method to identify innovative products using 2D scale. ANOVA or GPA is applied to understand consumer preferences for wine. Liking scores from RPM were comparable to liking scores from 9-point hedonic scale. Relative scoring improved ease of scoring difference and liking simultaneously. Abstract: At Australian wine shows, public tastings after formal judging provide an efficient condition for consumer preference testing to identify wine styles that are both liked and innovative. The aim of this study was to devise a method to conveniently obtain that information. We developed a new method, relative preference mapping (RPM), based on projective mapping and using relative scoring, to make the task cognitively less demanding. Using wine consumers, we tested the concept of a two dimensional (2D) labelled map to identify an innovative product and determined the level of difficulty in using a map scale.. The RPM method highlighted innovative wine styles – those wines that were simultaneously liked and considered different to a reference (gold medal wine). Liking results from the RPM method were similar to results from the traditional 9-point hedonic scale, providing validity for the preference component of the new method. RPM conveniently and simultaneously identifies preferred and innovative wine styles in a 2D product map, a unique contribution that no other scale is capable of achieving.